The Role of Nurses in Providing Family Planning Education Based on Literature Review - Feriani, Pipit (Health & Medical Sciences, 2026)
This study aims to analyze the role of nurses in providing family planning (FP) education through a comprehensive literature review approach. Using a qualitative descriptive method, the study synthesizes findings from peer-reviewed journals, academic books, and official reports published between 2019 and 2025 to explore how nurses contribute to enhancing reproductive health literacy and contraceptive awareness. Data were collected through systematic literature analysis, with inclusion criteria focusing on studies discussing nurse-led FP interventions in both clinical and community settings. The data were analyzed thematically through identification, categorization, and inductive synthesis of recurring patterns. The results reveal that nurse-led FP education significantly improves clients’ knowledge, attitudes, and decision-making autonomy regarding contraceptive methods. Nurses serve multiple roles as educators, counselors, and health promoters, bridging gaps between reproductive health knowledge and community practice. However, the study also identifies barriers such as limited training, insufficient institutional support, and cultural or moral influences that affect the consistency of FP counseling. Strengthening nursing education, continuous professional training, and competency-based curricula are key strategies for optimizing nurses’ performance in reproductive health programs. The findings contribute to advancing theoretical understanding of nursing’s educational role and offer practical recommendations for policy enhancement and curriculum development. Ultimately, the study reinforces that empowering nurses as FP educators is essential for promoting equitable, informed, and sustainable reproductive health outcomes.